CHARACTERIZATION OF BARK-MIDRIB FIBERS USING CHEMICAL TREATMENT VARIATIONS AS REINFORCEMENT IN BARK-MIDRIB FIBER COMPOSITES - -, Oliever (LPPM ITK, 2019)
Bark midrib are not fully utilized. Utilize the characterization of the fiber and process it into polymer composites with natural fiber reinforcement. The study was conducted using a variety of chemical treatments in the form of bark midribs without treatment, delignification treatment that is immersion using NaOH media concentration of 1%, 5%, 10% with 3 hours immersion time and bleaching treatment using H2O2 media 2% concentration with immersion time 30, 60 and 90 minutes. In obtaining suitable properties, tensile tests, impact tests, Scanning Electron Microscopy (SEM) images, and Fourier-Transform Infra-Red (FTIR) tests are performed. Optimal delignification treatment at 5% NaOH concentration with a tensile test value of 25.47 MPa (increasing 76.86%) and an impact test value of 11.95 kJ/m2 (increasing 11.45%). The optimal bleaching treatment at 90 minutes immersion with a tensile test value of 35.09 MPa (increased 36.36%) and impact test value of 13.77 kJ/m2 (increased 15.22%). The results of SEM images show that the bark midrib fiber composite without treatment has a lousy interface, delignification treatment with a reasonable good interface, and bleaching treatment with an excellent interface. FTIR test results showed that the bark midrib fiber composite without treatment had a cellulose component but hemicellulose and lignin levels still dominated. Based on the results of the study, bark midrib fiber with delignification chemical treatment using 5% NaOH for 3 hours followed by bleaching treatment using 2% H2O2 for 90 minutes is the treatment with the best results and then applied to a natural fiber composite product.